Practical Realization of Simultaneous Equations Solutions with Elimination Method and Its Effects on Students Performance in Some Selected Schools in Ekiti and Ondo States of Nigeria - O. O. Fagbohun; O. A. Oni (Archives of Current Research International, 2017)
Introducing students into Simultaneous equations and Matrices problem solving techniques without a practical way of transforming a real life physical system into the theory of what makes the subject, makes it so abstract and uninteresting, with many students avoiding its attempt in examinations. In order to redress the problem associated with abstract nature, a simultaneous equations and matrices training kits consisting of a simultaneous stepped-faced base, with a sizeable number of multi-colored cuboid inserted-numbered modeled cube, counters stand, counting number plates and arithmetic signs standing plates was developed for the practical teaching of Simultaneous equations in Schools. The two distinct differently colored cubes forms characters x and y to represent physical systems been used to represent values which of course are distinct from one another. 8 Secondary Schools in Ekiti and Ondo States of the Federal Republic of Nigeria with a class range of 82 to 124, with same teacher administering the subject over years, were selected for evaluation of the impact of the developed device in giving a clearer picture of the principles of solving simultaneous equations and matrices in order to strengthen students knowledge of applying the subject to varied physical problems. The percentage response of students that attempted, accurately solved the problems with and without the use of the kits were determined with respect to time of contacts. The results from the sampled Schools in use of the kits, shows that the total number of students attempt to questions on the Simultaneous equations in the whole class range between 80% and 91%, with between 82% and 97% correct solutions obtained, with between 3 and 4 contact class teachings of 45 minutes per class in comparison to the earlier 4 to 5 class teachings without the use of practical kits with between 22% and 40% of the total population of the school class well grounded in the methods of its solutions. Thus, the practical training kits improves the perception of the theory of Simultaneous equations, and strengthen the students in interpreting the underline principles.